Carboniferous palynoevents in the circum-Arctic region - Mangerud, Gunn; Lopes, Gilda; Bujak, Jonathan (Atlantic Geoscience, 2021)
The Carboniferous of the present-day Arctic yields an abundant and diverse association of terrestrial palynomorphs, particularly from Mississippian successions. Relatively few sections have been studied. However, those published so far demonstrate considerable similarities in the palynofloras between Arctic regions. Based on the published record, we present a compilation of 31 last occurrences (LOs), first occurrences (FOs), and some abundance events that have correlation potential around the Arctic. The chronostratigraphic resolution is relatively low, and the lack of independent age control hampers exact age assignments. But for most of these successions, palynology is the only dating tool available.